Analisis Sumber Daya Manusia dan Kompetensi terhadap Kualiats Kinerja Pegawai di BPPKAD Kabupaten Intan Jaya - Batau, Martina; Pasae, Yoel; Jaya, Amir (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of Human Resources (HR) and Competence on the Quality of Employee Performance at BPPKAD Intan Jaya Regency, both partially and simultaneously. The method used was quantitative with multiple linear regression analysis, involving 55 employees as a sample and questionnaire as a data collection tool. The results of the study showed that human resources had a positive and significant effect on the Quality of Employee Performance, with a standard Beta value of 0.260 and a significance of 0.042 (p < 0.05). T count 2.084 is greater than T table 1.67412, indicating that the improvement of human resources contributes to the improvement of the quality of employee performance. In addition, Competence also had a positive and significant effect, with a standard Beta value of 0.554 and a significance of 0.000 (p < 0.05). T count 4.445 is greater than T table 1.67412, indicating that improving competence significantly improves the quality of employee performance. Simultaneously, HR and Competency have a positive and significant effect on the quality of employee performance at BPPKAD Intan Jaya Regency. This confirms that good HR management and employee competency development are key to improving organizational performance.